Youths’ Perception of the Older People and Implications in Ekiti State (Nigeria) - Babatunde Joshua Omotosho; Roleola Tobiloba (Research on Ageing and Social Policy, 2024)
This study explored how young people perceive the older people and its implications on the lives of the older people in selected cities in Nigeria. Questionnaire were distributed amount 200 youths purposively selected in Oye and Ado Ekiti southwest Nigeria. In-depth interview sessions were equally conducted among 12 participants. Findings about youths’ engagements with the older people revealed that about 45 percent of the respondents felt the older people were difficult to please and too demanding; notwithstanding, a larger part of the respondents expressed a positive disposition about the older people. In-depth interview however revealed that many of the youths were not willing to have a close interaction with the older people as they considered them scary, old fashioned and too demanding. Many of the respondents attributed factors influencing their perception to family, personal experience and the media. From the older people perspective, in-depth interview revealed that the older people has not been receiving the needed supports from the youths and some of the implications include labelling; isolation, minimal support and stress. Youths’ negative perceptions about the older people are based on assumptions and media influences and not from direct experiences